1990
DOI: 10.1099/0022-1317-71-4-925
|View full text |Cite
|
Sign up to set email alerts
|

The nucleotide sequence of the genomic RNA of kennedya yellow mosaic tymovirus-Jervis Bay isolate: relationships with potex- and carlaviruses

Abstract: The nucleotide sequence of the genomic RNA of kennedya yellow mosaic tymovirus-Jervis Bay isolate (KYMV-JB) has been determined. The genome of KYMV-JB is 6362 nucleotide residues long and encodes three major open reading frames. The genomic organization and the encoded proteins of KYMV-JB are very similar to those of three other tymoviruses that have recently been reported. Sequence comparisons revealed that the possible replicase proteins of tymoviruses are closely related to those of potexviruses and carlavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Recently, a close relationship has been identified between the N-terminal domains of the respective proteins of potex-and tymoviruses (Rozanov et al, 1990;Ding et al, 1990). Here we report the results of computer-assisted compari-sons which expand each of these two families of Nterminal domains of viral replication proteins, demonstrate that they contain common sequence motifs and discuss their possible functions.…”
mentioning
confidence: 81%
“…Recently, a close relationship has been identified between the N-terminal domains of the respective proteins of potex-and tymoviruses (Rozanov et al, 1990;Ding et al, 1990). Here we report the results of computer-assisted compari-sons which expand each of these two families of Nterminal domains of viral replication proteins, demonstrate that they contain common sequence motifs and discuss their possible functions.…”
mentioning
confidence: 81%
“…The formation of hairpin structures upstream of the initiation site for sgRNA synthesis has been described or proposed for sg promoters of other viruses, e.g., the Bromoviridae (13), red clover necrotic mosaic dianthovirus (30), and TCV (28). Comparative secondary structure analyses in silico of a stretch of 90 nt of the minus-strand sequence containing the tymobox region of six different tymoviruses (TYMV [19]; Kennedya yellow mosaic virus, Jervis Bay isolate [9]; Ononis yellow mosaic virus [7]; eggplant mosaic virus [20]; Physalis mottle virus [12]; and Clitoria yellow vein virus [8]) revealed that the tymobox region could be involved in hairpin formation (not shown). To test whether the 4 nt of the initiation box are involved in important base pairing with nt 5608 to 5611 of the tymobox (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we report the complete genomic sequence of ELV, and compare that sequence with those reported for four other tymoviruses, namely eggplant mosaic virus (EMV-Trin; Osorio-Keese et al, 1989), kennedya yellow mosaic virus (KYMV-JB; Ding et al, 1990c), OYMV (OYMV-Tin; Ding et al, 1989) and TYMV (TYMV-CL; . The main aim of these comparisons was to search for specific sequence features that could be responsible for the biological similarities of ELV and TYMV-CL.…”
Section: Introductionmentioning
confidence: 99%